Electroencephalogram alertness responses to blue light stimulus in elderly people with cataract - Dong, Xuran; Wang, Minshu; Wang, Wei (Journal of clinical neuroscience, 2018)
•Day-time blue light increase alertness in elder people with significant cataracts.•Cataract surgery can increase blue light transmittance.•Blue light perception can be beneficial for the health of elder people. Daytime blue light exposure can reduce fatigue and increase alertness in young healthy adults. Little is known of the daytime blue light influence on alertness in elders. A prospective with-in subject study was carried out in Peking University Third Hospital to evaluate the impact of cataract surgery on visual functions and the electroencephalogram alertness response to blue light stimulus before and after surgery. 14 participants diagnosed with age-related cataract were scheduled for monocular cataract surgery with ultraviolet-filtering intraocular lens (IOL) implantation. Best corrected visual acuity (BCVA), color discrimination and electroencephalogram results were measured before and after surgery. Exposure to blue light resulted in decreased delta (0.25–3.00 Hz) activity and increased beta (13.25–30.00 Hz) activity both before and after cataract surgery. Significant improvements in the BCVA and Farnsworth-Munsell-100-hue total error scores were found after cataract surgery. The partial error scores in the red-yellow, green blue-blue, and blue purple-purple red bands also showed significant differences, with the green blue-blue band showing the most obvious improvement. Day-time blue light stimulus can increase alertness in elderly people with significant cataracts. Cataract surgery with ultraviolet-filtering IOL implantation can increase light, particularly blue light transmittance. Opaque lens removal does not increase the alertness responses to blue light 1 day after surgery. Nevertheless, the increase in light especially blue light perception can be beneficial for the health of elder people in the long run.